Determination of pullout resistance of galvanized-steel strips within select South African soils based on their free draining potential in mechanically stabilized earth wall backfill conditions - Hoffman, Kyle (Stellenbosch : Stellenbosch University, 2019)
Thesis (MEng)--Stellenbosch University, 2019.